2009
DOI: 10.1192/apt.bp.107.005421
|View full text |Cite
|
Sign up to set email alerts
|

Are you looking at me? Understanding and managing paranoid personality disorder

Abstract: SummARyParanoid personality disorder is a neglected topic in clinical psychiatry, and is often the subject of diagnostic confusion and therapeutic pessimism. This article presents a summary of the key diagnostic issues relating to paranoid personality disorder and describes various psychological and social processes mooted to be central to the genesis of paranoid thinking and behaviours. The evidence relating to paranoid personality disorder and risk of violence is summarised and clinically useful guidance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
0
12
0
11
Order By: Relevance
“…In a discussion of PPD in light of the transition from DSM-IV to 5, an argument was made to rethink PPD as the dimensional representation of trait-like suspicious hostility, rather than a categorical syndrome [1]. A recent review by Carroll [2] stressed its place in a pathway leading to violence in clinical and forensic settings. Bernstein and Useda [3] [3] provide a scholarly review of the rich psychological literature on PPD, and recalibrate the relationship between DSM-IV/5 descriptions and what is found in the population.…”
Section: Introductionmentioning
confidence: 99%
“…In a discussion of PPD in light of the transition from DSM-IV to 5, an argument was made to rethink PPD as the dimensional representation of trait-like suspicious hostility, rather than a categorical syndrome [1]. A recent review by Carroll [2] stressed its place in a pathway leading to violence in clinical and forensic settings. Bernstein and Useda [3] [3] provide a scholarly review of the rich psychological literature on PPD, and recalibrate the relationship between DSM-IV/5 descriptions and what is found in the population.…”
Section: Introductionmentioning
confidence: 99%
“…One such case report found cognitive analytic therapy to be an effective intervention (8), while another suggested that in the short-term, the use of antipsychotics in patients with paranoid personality disorder was associated with improved Clinical Global Impression scores (9). Cognitive therapy has been endorsed as a useful technique for the general psychiatrist (10). Recommended approaches to psychodynamic psychotherapy for these patients include working toward helping patients "shift their perceptions of the origin of their problems from an external locus to an internal one" (8), while maintaining special attention to management of boundaries, maintenance of the therapeutic alliance, safety, and awareness of how the therapy may be integrated into the patient's paranoid stance.…”
Section: Discussionmentioning
confidence: 99%
“…Podemos diferenciar a Perturbação Paranóide das outras perturbações de personalidade. A Perturbação Paranoide de Personalidade distingue-se da: (a) Perturbação Esquizóide de Personalidade na medida em que a característica mais saliente desta é o isolamento social, contudo os indivíduos com esta perturbação demonstram indiferença ao contacto com os outros, enquanto que a pessoa com PPP revela desconfiança das outras pessoas (Carroll, 2009); (b) da Perturbação Esquizotípica de Personalidade, na medida em que, embora partilhem a desconfiança, a ideação paranóide e o pouco envolvimento com os outros, nesta perturbação, ao contrário da PPP, o discurso, o próprio pensamento e a perceção das suas experiências são fora do comum (APA, 2013;Carroll, 2009); (c) da Perturbação Antissocial de Personalidade na medida em que ambas podem nutrir sentimentos de vingança frequentes, porém, na PPP há um pensamento e intensão mais paranóica e malévola (APA, 2013; Carroll, 2009); (d) da Perturbação Estado--Limite (Borderline) de Personalidade uma vez que, embora os indivíduos com essa perturbação quando se sentem stressados possam vir a expe-rimentar sentimentos de raiva e também ideias paranóides, no entanto, essas características não são persistentes como na PPP (Carroll, 2009); (e) da Perturbação Histriónica de Personalidade uma vez que também têm sentimentos frequentes de raiva, no entanto, não possuem desconfianças a nível global do comportamento das pessoas que os rodeiam como na PPP (APA, 2013); (f) da Perturbação Narcísica de Personalidade em que há uma preocupação maior em vangloriarem-se do que em duvidarem das intenções das pessoas que os rodeiam (típico da PPP). Em momentos de stress podem surgir algumas particularidades comuns à PPP (Young, Klosko, & Weishaar, 2003) (g) da Perturbação Evitante de Personalidade onde também existe desconfiança em relação às pessoas que a rodeiam devido ao receio de ser envergonhada pelos outros ou de a acharem inadequada.…”
Section: Diagnóstico Diferencialunclassified